Strength training for increased speed - Coultman, L. (Track Coach, 2018)
A primer for the use of strength training to develop speed. Strength training for speed is a topic that I always get questions about. Athletes want to know if they are performing the right exercises, how often they should train and how much they should lift. These are all legit questions, however strength training and workouts for speed are more complicated than that, and certainly includes more than simply lifting weights in the gym. Everyone within the sporting world would like to be faster. Whether its athletes on the track, footballers on the pitch or basketball players on the court, all athletes can highly benefit and increase their sporting performance by having this ability. Therefore it's important to understand what training procedures you need to have in place to allow for optimal adaptation of speed. In this article we will look at different types of strength training, why each type is beneficial for increasing